Trigliseridemia Postprandial Sebagai Faktor Prediksi Kejadian Kardiak Sindroma Koroner Akut Berulang - Muh A Sungkar; Harmani Kalim; Sjukri Karim (Jurnal Kardiologi Indonesia, 2008)
Background. Plasminogen Activator Inhibitor-1 (PAI-1) is an important hemostatic factor of thrombosis that inhibits fibrinolysis mechanism by tissue-Plasminogen Activator (t-PA). PAI-1 is a predictor for recurrentacute coronary syndrome (ACS). PAI-1 is also associated with Insulin Resistance syndrome that manifest as increase level of Triglyceride (Tg), decrease of HDL cholesterol, hypertension and glucose intolerance. Acute or chronic hypertriglyceridemia is often associated with high PAI-1 plasma activity. Objective. To know the relationship between postprandial Tg (ppTg) and increasing PAI-1 plasma levels in patients with ACS that may cause recur-rent cardiac events.MethodsThis is a case-control study, that included 54 ACS patients (aged 54-63 years), with or without ST segment elevation, without diabetes mel-litus, who were admitted to Emergency Department of National Cardiac Center Harapan Kita, Jakarta. All patients were followed up during hos-pitalization and one month after discharged. Subjects were divided into 2 groups based on ppTg level and compared it to age group, sex, body mass index, smoking habit, systolic blood pressure, pulse, ST segment deviation, CKMB, total cholesterol, low density lipoprotein (LDL), HDL and PAI-1 levels, as haemostatic factor. Patients with ppTg level < 153.5 mg/dL is a control case. Results.There was an increasing PAI-1 levels (mean 28.9 ± 25.81 ng/dL) as predictor of post ACS events in the study subjects. The level of PAI-1 plasma increased in patients with hypertriglyceridemia (p=0.004). Despite no significant association between pp hipertriglicerydemia and MACE, the overall results showed a significant association between postprandial hipertriglicerydemia and obesity (p=0.037) as well as HDL cholesterol as components of metabolic syndrome. Conclusions. The postprandial hipertriglicerydemia is a condition that can be found in metabolic disturbances and may influence coagulation status. There are association between pp hipertriglicerydemia and obesity. PAI-1 level is predictor for recurrent cardiac events post ACS.